INTERTEXTUALITY IN LITERARY WORKS: THE INTEGRATION OF HISTORY, ART, AND FOLK WISDOM IN SHAYTANAT (Devildom) by TOHIR MALIK (International conference on multidisciplinary science, 2025)
This paper explores the concept of intertextuality within literary works and the function of intertextual components. Elements of intertextuality (such as allusion, reminiscence, epigraph, oxymoron, and more) enhance the expressiveness of a piece, offer supplementary information, and are crucial for maintaining the overall coherence of the text. These techniques assist readers in grasping the work more effectively and make the text more captivating and enriched.